Scientific information and cognitive bias in the case of New Breeding Techniques: Exploring Millennials behaviour in Italy - Federica De Maria; Annalisa Zezza (Italian Review of Agricultural Economics (REA), 2022)
The paper explores consumers' acceptance of New Breeding Techniques (NBTs) in the agri-food sector. Our main research question concerns the role of information in shaping consumers' attitude towards genetically modified food and new breeding techniques in agricultural production. To this extent, we use a Multinomial Logit Model to analyse changes or confirmations of prior opinions on food safety concerns and environmental risks associated with modern biotechnologies once scientific information has been provided. Our findings confirm the Bayesian hypothesis according to which people combine their prior belief with new information to converge scientific information in the case of food safety. We also found a higher probability of confirmation bias, with people less willing to change their prior beliefs, when environmental risks are concerned.
Keywords: B4; Q5; Q00; 330; Genome Editing; millennials; food safety; environmental risks; biotechnology; Multinomial Logistic Regression